Strategic Integration of Policy and Logistics: A Case Study of Copenhagen’s Model for Sustainable Urban Supply Chains - Luluk Fauziah; Mashudi Mashudi; Tri Yuniningsih (Khazanah Sosial, 2024)
This study explores integrating logistics policies and practices in creating efficient and sustainable urban supply chains. The study analyzes how green transport policies, the use of digital technologies, and collaboration between government and the private sector contribute to improving logistics efficiency and reducing emissions through a qualitative approach with thematic interviews with stakeholders and a case study of Copenhagen. Copenhagen has successfully implemented low-emission zones and an intelligent traffic management system that optimizes delivery routes, thereby reducing congestion and increasing sustainability. The findings provide important insights for other cities, including Jakarta, that face similar challenges in the logistics sector. The study suggests that implementing an effective policy integration model can help address environmental and operational issues, as well as improve the quality of life for urban residents. The results of this study contribute to the literature on urban logistics and sustainability policies and offer strategic recommendations for policymakers.